Flexible power control strategy for elliptical trajectory based dynamic voltage restorer during voltage sags. Issue 13 (27th May 2021) - Li, Peng; Wang, Yi; Wang, Can; Pan, Xuewei; Lu, Jinghang; Li, Xue; Blaabjerg, Frede
Abstract: Dynamic voltage restorer (DVR) plays an essential role in achieving high‐quality voltage restoration in the distribution system. This paper presents an elliptical‐trajectory‐based approach to guarantee continuous power delivery by considering the active and reactive power limits during voltage sags. Besides, two parameters are proposed in the accurate mathematical analysis of current references. Thus, the control objective can be fulfilled by the flexible current injection strategy that combines a precise balance between the positive and negative sequences. The proposed control method can determine the required power injections by selecting the two proper values to support that the converter output current is smaller than the maximum rated value. Under the presented control, the maximum power limit and flexible power dispatch are combined together to develop four operation schemes. The main advantage is the smooth transition process during changes in the operation schemes and the disappearance of active and reactive power oscillations. Also, these four control states are applied to reveal the flexibility of the proposed designs. Finally, the hardware tests in a laboratory prototype are implemented to validate the feasibility of the proposed method.